Timing of posterior parahippocampal gyrus activity reveals multiple scene processing stages - Bastin, Julien (Hum Brain Mapp, 2012)
Posterior parahippocampal gyrus (PPHG) is strongly involved during scene recognition and spatial cognition. How PPHG electrophysiological activity could underlie these functions, and whether they share similar timing mechanisms is unknown. We addressed this question in two intracerebral experiments which revealed that PPHG neural activity dissociated an early stimulus‐driven effect (>200 and <500 ms) and a late task‐related effect (>600 and <800 ms). Strongest PPHG gamma band (50–150 Hz) activities were found early when subjects passively viewed scenes (scene selectivity effect) and lately when they had to estimate the position of an object relative to the environment (allocentric effect). Based on single trial analyses, we were able to predict when patients viewed scenes (compared to other visual categories) and when they performed allocentric judgments (compared to other spatial judgments). The anatomical location corresponding to the strongest effects was in the depth of the collateral sulcus. Our findings directly affect current theories of visual scene processing and spatial orientation by providing new timing constraints and by demonstrating the existence of separable information processing stages in the functionally defined parahippocampal place area. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.